Cervical consistency index and risk of Cesarean delivery after induction of labor at term. (6th June 2019) - Migliorelli, F.; Rueda, C.; Angeles, M. A.; Baños, N.; Posadas, D. E.; Gratacós, E.; Palacio, M.
ABSTRACT: Objective: To evaluate the association between the cervical consistency index (CCI) and the risk of Cesarean delivery after planned induction of labor (IOL) at term. Methods: This was a prospective observational study of women with a term singleton pregnancy admitted for IOL due to maternal or fetal indication. Ultrasonographic images were obtained before IOL and CCI was calculated offline once recruitment was completed. The main outcome was defined as Cesarean delivery due to failed IOL or arrest of labor. Cesarean deliveries indicated due to maternal or fetal compromise (Van Dillen's grade 1 or 2) were excluded from analysis. Univariate statistical analysis was performed using Fisher's exact test and Student's t ‐test for categorical and continuous variables, respectively. Multivariate analysis was performed using logistic regression, including CCI and other variables related to the main outcome. Intraclass correlation coefficients were used to estimate intra‐ and interobserver agreement. Results: Of 510 women admitted for IOL during the study period and for whom image quality was adequate, 46 were excluded due to emergency Cesarean delivery leaving 464 pregnancies for analysis. Cesarean section due to failed IOL or arrest of labor was performed in 100/464 (21.6%) pregnancies. The mean CCI of women who underwent Cesarean delivery was not significantly different from that in those who had vaginal delivery after IOL (70.1 ± 12.3% vs 70.0 ± 13.1%; P = 0.94). Multivariate analysis also showed absence of statistical association between CCI and Cesarean delivery for failed IOL or arrest of labor. Intraclass correlation coefficients for intra‐ and interobserver agreement were 0.81 (95% CI, 0.66–0.89) and 0.86 (95% CI, 0.75–0.92), respectively. Conclusion: CCI does not seem to be associated with the risk of Cesarean delivery after IOL. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.